The Influence of Realistic Mathematical Approach to Understanding Concept and the Mathematical Connection Ability of Islamic Private Vocational School Students Hikmatul Fadhillah Medan Class VII - Siska Adliani; Asmin Asmin; Hasratuddin Hasratuddin (BIRCU, 2020)
The purpose of this research in the design of Quasi Experiment is to investigate the effect of the Realistic Mathematical Approach (PMR) on the ability to understand students' mathematical concepts, the ability of students' mathematical connections and the interaction between learning approaches with students' initial abilities on the differences in the influence of students' understanding abilities and students' mathematical connections. The research was carried out at Hikmatul Fadhillah Islamic Private Middle School in class VII with 118 students. This research is an experimental study with a test-post-test control group design research design. The population in this study were all students of class VII by taking a sample of two classes (experimental class and control class) through random sampling techniques. Data obtained through KAM test, mathematics concept comprehension ability test, and mathematics connection ability test. Data were analyzed by two-way ANAVA test. Before using the two-way ANAVA test homogeneity tests were used in the study and normality in this study was 5% significant. The results of data analysis showed that the average concept comprehension ability test was 71.43 and the control class was 62.54, with a value of sig = 0 with 0 <5 0.05, so there was a difference in the effect of students' understanding of mathematics concepts being taught with a mathematical approach realistic mathematics (PMR) with the usual learning approach, the average test ability of experimental and control mathematical connections is 70.43 and 67.76 with sig = 0, with 0 <∝ 0.05, then there are differences in the effect of students' mathematical connection abilities taught with a realistic mathematics approach (PMR) and conventional learning approach, a significant value of 0.127, because 0.127> 0.05